Knowledge Sharing Sebagai Sumber Inovasi dan Keunggulan Bersaing Pada Usaha Mikro Kecil dan Menengah (UMKM) Sektor Batik - Drs. M. Assegaf, MM -; Dra. Wasitowati, MM - (Conference In Business, Accounting, And Management (CBAM), 2015)
Small and medium batik sector are significantly contribution to econo mic development and the cultural heritage, but development are still many prob lems, especially the empowerment of internal assets so it has an impact on the development of innovation capability ann competitive advantage. This study aims to examine the effect of knowledge sharing process to innovation capability and competitive advantage at small and medium batik sector in Central Java. Sampling methods using purposive sampling and data analysis using the Partial Least Square (PLS). The research results that knowledge donataing and knowledge collecting are significantly effect on innovation capability. Knowledge donating, knowledge collecting and innovation capability are significantly effect on the competitive advantage. Keywords: Knowledge collecting , Knowledge donating, Innovation capability